Ghrelin against alendronate-induced gastric damage in rats - YEGEN, BERRAK; ŞENER, GÖKSEL (BIOSCIENTIFICA LTD, 2005)
Alendronate sodium, a primary amino bisphosphonate, is widely used in the treatment of various diseases that are associated with bone resorption, such as postmenopausal osteoporosis and Paget's disease of bone. Although the adverse effects of biphosphonates on the gastrointestinal system have been demonstrated in experimental and clinical studies, the exact mechanisms underlying this damage are not clear yet. Ghrelin, a 28 amino acid peptide produced predominantly by the stomach, was shown to exert a potent protective action on the stomach of rats exposed to ethanol or stress. Our objective was to evaluate the possible antioxidant and anti-inflammatory effects of ghrelin against alendronate-induced gastric darnage. Wistar albino rats were administered alendronate (20 mg/kg) by gavage for 4 days, along with either ghrelin (10 ng/kg per day) or saline given i.p. After decapitation, stomach tissues were removed for the determination of malondialdehyde (MIDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and tissue collagen content, while the extent of tissue damage was analyzed microscopically. Formation of reactive oxygen species was determined by chemiluminesence using a Iuminol probe in fresh gastric tissues. Serum tumor necrosis factor (TNF-alpha) and lactate dehydrogenase levels were assessed in trunk blood. Oral administration of alendronate-induced significant gastric damage, accompanied by increased MPO activity, collagen content, MIDA and luminol levels (P < 0(.)01 < P < 0(.)001), while tissue GSH was decreased (P < 0(.)01). On the other hand, ghrelin treatment reversed these alterations (P < 0(.)05-P < 0(.)001) as well as elevating serum TNF-alpha levels significantly (P < 0(.)001). The findings of the present study suggest that alendronate induces oxidative gastric damage by a local irritant effect, and ghrelin amellorates this damage by its possible antioxidant and anti-inflammatory properties.
Keywords: POSTMENOPAUSAL WOMEN; CIRCULATING GHRELIN; OXIDATIVE STRESS; ACID-SECRETION; GROWTH-HORMONE; BISPHOSPHONATES; MECHANISMS; STOMACH; MUCOSA; INJURY